Does Input Tariff Reduction Impact Firms Exports in the Presence of Import Tariff Exemption Regimes? - Cruz, Marcio (World Bank, Washington, DC, 2015)
In the last decade Morocco undertook substantial, if gradual, trade liberalization by reducing tariffs, reforming trade regulations and signing free and preferential trade agreements with several regions and countries, including the United States, Turkey, the European Union and Arab countries. This paper analyzes the impact of input tariff reduction on Moroccan exporting firms through the channel of intermediate goods. Gaining access to more varied and cheaper inputs can make exporting firms more competitive, and as a result they export more. To evaluate how this policy may impact firms export performance, the paper analyzes the impact of input tariff reduction on different margins of trade with emphasis on export markets and product diversification. The identification of the effect of input tariffs on exports relies on a difference-in-difference estimator using heterogeneous access to import tariff exemption as a measure of different levels of exposure to input tariff reduction at the firm level. Overall, the analysis finds that firms that are relatively more exposed to input tariff perform better in those sectors with the largest input tariff reduction, with better access to markets, higher probability to survive when exporting new products in those sectors and higher export value growth.